Antistatic and antibacterial biaxially stretched polyester composite film and preparation method thereof

By designing the composite structure of the anticidarity layer, primer layer, and polyester base layer in the polyester film, build a layered self -assembly system, solve the problem of insufficient anticoor static and antibacterial properties in existing technologies, and realize the polyester composite film. Excellent anticidering and long -acting antibacterial effects.

CN116655983BActive Publication Date: 2025-01-28ZHEJIANG HESHUN NEW MATERIAL CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310586580.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-24
Publication Date
2025-01-28
Estimated Expiration
2043-05-24

AI Technical Summary

Technical Problem

It is difficult to design and prepare polyester films that have both antistatic functions and excellent and long-term antibacterial properties in the prior art.

Method used

The composite structure of antistatic layers, primer layers, and polyester base layers is adopted to build a layered self -assembly system through specific raw materials and process preparation to improve the antichattering and antibacterial performance. Specifically, the use of copper ions with bacteria in the anti -static layer to destroy the bacterial structure, and through the triaxy hydroxyamine hydrochloric acid, polybaramine and polyethylene amine, and seaweed in the electrostatic layer in the bottom paint layer Sodium and gallel oxide construct a layered system to control the release speed of copper ions.

Benefits of technology

The excellent antistatic performance and long -acting antibacterial performance of the polyester composite film are realized, and the problem of being released by too fast copper ions is avoided, and the overall mechanical properties and durability of the film are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116655983B_ABST
    Figure CN116655983B_ABST
Patent Text Reader

Abstract

The present invention relates to an antistatic and antibacterial biaxially stretched polyester composite film and a preparation method thereof, wherein the polyester composite film comprises in sequence: an antistatic layer, a primer layer and a polyester base layer; the antistatic layer, in parts by weight, comprises: 10-20 parts of a cross-linked resin, 5-15 parts of sodium alginate, 5-15 parts of graphene oxide, and 2-10 parts of copper sulfate; the primer layer, in parts by weight, comprises: 10-20 parts of a cross-linked resin, 5-15 parts of polydopamine, 5-15 parts of branched polyethyleneimine, and 1-10 parts of trishydroxymethylaminomethane hydrochloride; the mass ratio of isocyanate resin, polyester resin and polyacrylic resin in the cross-linked resin is (1-5): (1-5): (1-10). The present invention introduces functional components such as metal ions, which not only improves the antistatic and antibacterial properties of the film, but also avoids the excessive release of functional components through a self-assembly system, thereby obtaining excellent long-acting antistatic and antibacterial properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyester-based composite films, and in particular relates to an antistatic and antibacterial biaxially stretched polyester composite film and a preparation method thereof. Background Art

[0002] Biaxially oriented polyester film is a high-end film that is made of glossy material (that is, by adding titanium dioxide to the raw material polyester chips to improve the heat resistance, light resistance and weather resistance of plastic products) through drying, melting, filtering, extrusion, casting, longitudinal and transverse stretching to winding. It has excellent mechanical properties, high rigidity, hardness and toughness, good puncture resistance, friction resistance, high and low temperature resistance, chemical resistance, oil resistance, air tightness and fragrance retention. It is one of the commonly used barrier composite film substrates.

[0003] Static electricity is widely present, which may cause harm or catastrophic consequences to people's health and safety, and cause irreparable damage to electronic equipment and industrial production. In the manufacturing and processing of polyester film, due to the presence of organic solvents, there is a risk of fire when static electricity is discharged. At the same time, the film may absorb impurities or dust due to static electricity, which in turn affects the relevant properties of the film. Therefore, electrostatic discharge protection technology is of great significance in industrial workshops and equipment, plastics, electronic products, etc.

[0004] According to different usage methods, antistatic agents can be divided into external coating type and internal mixing type. External coating type antistatic agent refers to a type of antistatic agent used on the surface of polymer materials. Generally, the antistatic agent solution of a certain concentration is attached to the surface of the polymer material by coating, spraying or dipping, and then dried at room temperature or hot air to form an antistatic coating. When the antistatic agent solution is impregnated with the polymer material, the lipophilic groups in the antistatic agent molecules will be adsorbed on the surface of the material, and the hydrophilic groups in the antistatic agent molecules are arranged toward the air side, which is easy to absorb environmental moisture, or combine with moisture in the air through hydrogen bonds to form a monomolecular conductive layer, so that the generated static charge leaks quickly to achieve the purpose of antistatic. Internal mixing type antistatic agent refers to a type of antistatic agent added to the resin during the processing of the product. In addition to giving the surface of the polymer material a certain lubricity, reducing the friction coefficient, and inhibiting and reducing the generation of static charge, different types of antistatic agents have different chemical compositions and usage methods, as well as different mechanisms of action. Patent CN213113177 U discloses an antistatic polyester film, which has a multi-layer structure, and its electrostatic layer contains a cationic polymer antistatic agent, which effectively improves the antistatic property of the polyester film. At the same time, an innovative glue layer is designed, in which an antistatic agent is added, which effectively reduces the situation in which the glue layer absorbs impurities when the polyester film is used, resulting in poor adhesion.

[0005] On the other hand, bacteria exist in large numbers in the environment, and epidemic diseases caused by bacteria spread faster and faster, and the scope of impact is also getting larger and larger. Mobile phones, smart terminal devices in public places, etc. are used frequently, providing a wide range of transmission channels for bacteria. Existing antibacterial films are mainly prepared by direct mixing, surface chemical modification, and surface coating. The direct mixing method is to directly mix and add antibacterial functional substances to polymer materials, and then obtain antibacterial films through various molding processes. This method has high requirements on the performance of antibacterial agents and is technically difficult. The surface chemical modification method is to graft or fix the antibacterial functional substances on the film substrate in the form of chemical bonds, which requires the antibacterial agent and the matrix material to meet specific conditions. Most of them need to introduce active groups in advance, the degree of chemical grafting is difficult to control, the reaction process and mechanism are complex, and the practical application is difficult, which is not conducive to large-scale promotion and use. The surface coating method, which is currently more commonly used, has a short antibacterial effect and cannot meet the needs of long-term antibacterial use. Patent CN183831221B discloses a method for preparing an antibacterial film, wherein a nano antibacterial coating is applied to the surface of a biaxially stretched polypropylene film or polyester film, wherein the active ingredients include nano titanium oxide, nano silver, nano aluminum and a combination thereof. Unmodified inorganic nanoparticles are very easy to agglomerate, and the antibacterial agent is not easy to disperse evenly, which affects the antibacterial properties of the antibacterial film.

[0006] Therefore, how to design and prepare polyester film products that have both antistatic function and excellent and long-lasting antibacterial properties has become a technical problem that needs to be urgently solved in this field. Summary of the invention

[0007] In view of the defects existing in the above-mentioned prior art, the purpose of the present invention is to provide an antistatic and antibacterial biaxially stretched polyester composite film and a preparation method thereof. The present invention sets the polyester composite film to at least include an antistatic layer, a primer layer and a polyester base layer, and prepares the antistatic layer, the primer layer and the polyester base layer by selecting specific types of raw materials, and adopts a preparation method combining coating with stretching, and combining pre-drying with co-curing. The prepared polyester composite film has good interlayer compatibility and bonding force, especially excellent antistatic performance, and excellent and long-lasting antibacterial properties.

[0008] Specifically, an antistatic and antibacterial biaxially stretched polyester composite film comprises the following layers in sequence: an antistatic layer, a primer layer and a polyester base layer;

[0009] The antistatic layer has a thickness of 5-20 μm and comprises, by weight:

[0010]

[0011] The primer layer, with a thickness of 5-20 μm, comprises, by weight:

[0012]

[0013] Polyester base layer, thickness 10-25μm;

[0014] The cross-linked resin is prepared by cross-linking and curing -NCO in isocyanate resin with polyester resin and polyacrylic resin, and the mass ratio of isocyanate resin, polyester resin and polyacrylic resin is (1-5): (1-5): (1-10).

[0015] The antistatic and antibacterial biaxially stretched polyester composite film provided by the present invention adopts a specific structure and raw materials, so that the positively charged copper ions contact the negatively charged bacterial surface, destroy the bacterial surface structure, cause the cell fluid to flow out, and cause the bacteria to die. At the same time, the copper ions entering the bacterial cells can react with the protein enzymes in the bacterial cells, causing the enzymes to denature and inactivate, thereby killing the bacteria. Tris(hydroxymethyl)aminomethane hydrochloride), polydopamine, and branched polyethyleneimine are added to the base coat, and sodium alginate, graphene oxide, and copper sulfate are added to the electrostatic layer to construct a hierarchical self-assembly system to control the metal ion release rate to achieve a more lasting antibacterial performance.

[0016] The coating self-assembled by Michael addition reaction of polydopamine and branched polyethyleneimine is firmly bonded to the surface of the film substrate, providing a cationic polyelectrolyte. 3+ ), the amino group undergoes a condensation reaction with the dopamine molecule in an alkaline medium to form a cross-linked polymer. In the Michael addition reaction, the electrophilic conjugated system (electron acceptor) and the nucleophilic ion (electron donor) undergo a conjugate addition reaction. The dopamine molecule provides the nucleophilic ion, and the amino group (NH 3+ ) is an electrophilic conjugated system (electron acceptor).

[0017] Sodium alginate and graphene are rich in -COOH groups, which can form hydrogen bonds with copper ions for self-assembly, providing anionic polyelectrolytes. Combining with the former through electrostatic force to construct a hierarchical self-assembly system can prevent the copper ions from being released too quickly, improve the antibacterial efficiency, avoid the addition of too many copper ions affecting the surface morphology of the film, and promote a stronger combination of the bottom coating and the electrostatic layer. In addition, the hierarchical self-assembly system can improve the surface hydrophilicity of the polyester composite film and enhance the antistatic performance of the polyester composite film.

[0018] The "hierarchical self-assembly system" referred to in the present invention means that the polydopamine-branched polyethyleneimine copolymer is formed in the primer layer as a cationic polyelectrolyte, and the sodium alginate and graphene oxide in the antistatic layer are rich in -COOH groups that can form hydrogen bonds with copper ions and the like for self-assembly, providing anionic polyelectrolytes, thereby promoting a more solid combination of the primer layer and the antistatic layer.

[0019] Further, the cross-linked resin of the antistatic layer and the cross-linked resin of the primer layer are prepared by UV cross-linking and co-curing after the composite film is biaxially stretched. The cross-linked resin of the antistatic layer of the present invention and the cross-linked resin of the primer layer can have exactly the same composition, or can be slightly different in proportion. According to the excellent compatibility of the same components, the antistatic layer and the primer layer have excellent compatibility. In addition, by co-curing, a cross-linked structure is formed between the layers, which further improves the interlayer bonding force and effectively improves the peel strength.

[0020] Preferably, the polyester resin used in the present invention can be a known polyester resin, which is formed by polycondensation of at least one component selected from terephthalic acid, phthalic anhydride, trimellitic anhydride and at least one component selected from ethylene glycol, propylene glycol, glycerol, 1,6-hexanediol, 1,2-butanediol. The polycondensation reaction is not described here, and those skilled in the art can select it in the prior art according to actual needs. As a preferred technical solution, the polyester resin is selected from polyethylene terephthalate (PET).

[0021] The polyacrylic resin is prepared by polymerizing at least one of methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, and acrylamide. The polymerization reaction will not be described in detail here, and those skilled in the art can select from the prior art according to actual needs.

[0022] The isocyanate resin is prepared by polymerizing at least one of toluene diisocyanate, diphenylmethane diisocyanate, polymethylene polyphenyl polyisocyanate, hexylene diisocyanate, xylylene diisocyanate, and isophorone diisocyanate.

[0023] Generally speaking, polyester resin and polyacrylic resin have low solubility in water, and the introduction of hydrophilic groups and / or their oligomers is conducive to their dispersion in water. The -NCO groups in the isocyanate resin molecular chain can undergo crosslinking and curing reactions with polyacrylic resin and polyester resin to form a crosslinked network structure, thereby improving the stability of the primer layer and the antistatic layer. For example, the isocyanate resin is selected from a water-dispersible isocyanate curing agent, and aliphatic or alicyclic polyisocyanates (such as HDI or IPDI) can be modified by aminosulfonates to improve the hydrophilicity of the isocyanate resin.

[0024] Furthermore, the surface of the polyester base layer opposite to the primer layer also includes a glue layer with a thickness of 5-15 μm, which includes a polyurethane resin and an antistatic agent. The antistatic agent includes an amphoteric antistatic agent, and its content accounts for 20-50% of the total mass of the glue layer.

[0025] Preferably, the polyurethane resin is selected from at least one of diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI) and polypropylene glycol (PPG). The antistatic agent is preferably an amphoteric antistatic agent, such as betaine, alkyl imidazolinium salt and alkyl amino acid, which contains both cationic and anionic groups in the molecule and can simultaneously exhibit cationic and anionic antistatic effects under certain conditions, and has strong adhesion to polymer materials.

[0026] Well-known water-based polyurethane resins such as water-based vinyl polyurethane adhesives, sulfonic acid anionic polyurethane emulsions, etc. are used. They are rich in -COOH, -OH and other groups, have strong hydrophilicity, and have good dispersibility in aqueous solution.

[0027] Furthermore, nano-copper oxide and / or nano-cuprous oxide are deposited on the surface of the graphene oxide, and the total mass ratio of the nano-copper oxide and nano-cuprous oxide to the mass ratio of the graphene oxide is 1:(10-20); the particle size of the nano-copper oxide and nano-cuprous oxide is ≤50nm.

[0028] While using copper particles as an antibacterial agent, the long-lasting antibacterial effect can be further enhanced by depositing nano-copper oxide and / or nano-cuprous oxide on the surface of graphene oxide. Graphene oxide material is a single layer of carbon atoms tightly stacked into a two-dimensional honeycomb structure. Graphene oxide has a large specific surface area and porosity. On the one hand, it can be used as a good carrier for loading CuO / Cu2O nanoparticles. On the other hand, the graphene oxide material sheet contains a large number of functional groups, such as hydroxyl, carboxyl, carbonyl, etc., which can adsorb the surface of bacteria or viruses and isolate bacteria or viruses, thereby playing the role of isolation, sterilization or disinfection.

[0029] CuO / Cu2O nanoparticles are highly effective inorganic fungicides. During use, the copper ions or cuprous ions seeped out of the CuO / Cu2O nanoparticles can be adsorbed onto the spike protein of the virus or the envelope protein or cell wall of the pathogen through electrostatic adsorption, destroying the surface protein structure of the virus or bacteria, and achieving antibacterial and antiviral effects.

[0030] However, CuO / Cu2O nanoparticles have the disadvantages of being easy to agglomerate and releasing ions too quickly. In order to give full play to the long-term antibacterial performance of CuO / Cu2O nanoparticles, the present invention prepares graphene oxide with long-term antibacterial activity of nano copper oxide and nano cuprous oxide by depositing CuO / Cu2O nanoparticles on the surface of graphene oxide. Graphene oxide provides a protective barrier for CuO / Cu2O nanoparticles, preventing CuO / Cu2O nanoparticles from directly contacting and reacting with the outside and leaching copper ions too quickly. At the same time, CuO / Cu2O nanoparticles are firmly bound to the surface of graphene oxide through electrostatic action, thereby improving its dispersibility.

[0031] In addition, graphene oxide-loaded CuO / Cu2O nanoparticles can form holes under visible light or near-infrared light, which in turn promotes the generation of active groups such as reactive oxygen and hydroxyl radicals, which then act on bacteria or viruses through the active groups, playing an antibacterial and antiseptic role. Under visible light or near-infrared light, CuO / Cu2O nanoparticles also have good photothermal conversion effects, playing a photothermal disinfection or antibacterial role.

[0032] Preferably, nano-copper oxide and nano-cuprous oxide are deposited on the surface of the graphene oxide, and the deposition is carried out through the following steps:

[0033] (1) preparing a copper salt solution with a mass percentage concentration of 5-15%, dividing it into two parts, adding graphene oxide to the first copper salt solution, and ultrasonically shaking and stirring at high speed;

[0034] (2) adding polyethylene glycol to the first copper salt solution, stirring and drying at 80-120° C., treating at 500-600° C. for 1-2 h, and grinding to obtain graphene oxide-nano copper oxide powder;

[0035] (3) dispersing the graphene oxide-nano copper oxide powder obtained in step (2) in the second copper salt solution;

[0036] (4) preparing a sodium alginate solution with a mass percentage concentration of 5-15%, adding the copper salt solution of step (3) into the sodium alginate solution, adding a reducing agent and reacting for 20-60 minutes to obtain graphene oxide with nano-copper oxide and nano-cuprous oxide deposited on the surface.

[0037] In order to load CuO / Cu2O nanoparticles on the surface of graphene oxide, the method of preparing graphene oxide-nano copper oxide powder and graphene oxide-nano cuprous oxide powder respectively can be adopted, and then one or two of them are selected for use. However, in order to reduce the process steps and reduce the cost, the method of directly preparing graphene oxide of nano copper oxide and nano cuprous oxide is more preferred. In addition, by using an excess copper salt solution, it is not only easy to control the amount of generated nanoparticles, but also after the nanoparticles are deposited, the remaining copper salt in the solution can be directly used as a matrix solution to provide copper ions.

[0038] In order to prepare the aforementioned antistatic and antibacterial biaxially stretched polyester composite film at low cost, high efficiency and stability, the present invention further provides a method for preparing the antistatic and antibacterial biaxially stretched polyester composite film, which comprises the following steps:

[0039] S1: using polyester masterbatch to melt and extrude into film through an extruder, and cooling and shaping on a chilled roller to obtain a polyester base layer;

[0040] S2: applying the coating liquid of the primer layer to a surface of the polyester base layer, pre-drying, and stretching along a first direction;

[0041] S3: applying the coating liquid of the antistatic layer to the outer surface of the primer layer, pre-drying, stretching along a second direction perpendicular to the first direction, and heat treating to fix the shape;

[0042] S4: UV cross-linking and curing to obtain an antistatic and antibacterial biaxially stretched polyester composite film.

[0043] The coating method adopted by the present invention is an online coating method. The coating obtained by online coating is uniform and thin, with fast coating speed, high efficiency and low cost. The present invention preferably adopts a rod coating method to apply a primer layer to one surface of the polyester base layer, and then pre-dry under certain conditions, stretch along the mechanical direction, and cool at room temperature. The antistatic layer is coated on the upper surface of the primer layer by the rod coating method again, pre-dried, stretched in the transverse direction, and then heat-treated and shaped in a tentering machine, and then ultraviolet curing is performed. The UV light source is selected from at least one of a mercury lamp light source, an LED light source, and a xenon lamp light source, and the curing energy is 2000-12000mJ / cm 2 .

[0044] In order to facilitate stretching, pre-drying can be carried out in the following ways to reduce the fluidity of the coating, facilitate stretching and form a uniformly stretched layer:

[0045] 1) Raise the temperature to 110-150°C at 1-2°C per second for pre-drying;

[0046] 2) Use ultraviolet light curing agent and ultraviolet light pre-curing, and control the curing degree at 10-30%.

[0047] According to the steps of the preparation method, the pre-drying of the primer layer in step S2 is preferably carried out by UV pre-curing to avoid incomplete UV curing when the antistatic layer is laminated and UV co-cured. The pre-drying method of the antistatic layer as the top layer can be either of the two methods.

[0048] As mentioned above, the antistatic and antibacterial biaxially stretched polyester composite film of the present invention may also include a glue layer, the raw materials of which include polyurethane resin, antistatic agent and silicone wetting agent, the antistatic agent includes an amphoteric antistatic agent, and the content accounts for 20-50% of the total mass of the glue layer. The relevant contents of the antistatic agent and the polyurethane resin have been recorded above and will not be repeated here. The application of the glue layer is optional: 1) while the antistatic layer is applied with a rod in step S3, an optional glue layer is applied on the surface of the polyester base opposite to the primer layer, and then dried together with the antistatic layer, stretched along the second direction, and then heat-treated for finalization; 2) after stretching along the second direction in step S3, the surface of the polyester base opposite to the primer layer is coated, and then heat-treated for finalization; or 3) it is carried out separately after the ultraviolet cross-linking curing in step S4, and it is necessary to increase the drying and finalization link at this time. The preferred method 1) saves the coating link and reduces the preparation time.

[0049] Furthermore, the coating liquid of the antistatic layer comprises, by weight percentage:

[0050]

[0051] The resin to be cross-linked includes isocyanate resin, polyester resin and polyacrylic resin, and the mass ratio of isocyanate resin, polyester resin and polyacrylic resin is (1-5): (1-5): (1-10).

[0052] Furthermore, the coating liquid of the antistatic layer is prepared by the following steps:

[0053] (1) preparing a copper sulfate solution with a mass percentage concentration of 5-15%, dividing it into two parts, adding graphene oxide to the first copper sulfate solution, and ultrasonically shaking and stirring at high speed;

[0054] (2) adding polyethylene glycol to the first copper sulfate solution in which graphene oxide is dispersed, stirring and drying at 80-120° C., treating at 500-600° C. for 1-2 h, and grinding to obtain graphene oxide-nano copper oxide powder;

[0055] (3) dispersing the graphene oxide-nano copper oxide powder obtained in step (2) in a second portion of the copper sulfate solution;

[0056] (4) preparing a sodium alginate solution with a mass percentage concentration of 5-15%, adding the copper sulfate solution of step (3) to the sodium alginate solution, adding a reducing agent to react for 20-30 minutes, and obtaining graphene oxide with nano-copper oxide and nano-cuprous oxide deposited on the surface; the reducing agent is ascorbic acid and / or glucose, and the molar ratio of the reducing agent to copper sulfate is 1:(4-8);

[0057] (5) Add the resin to be cross-linked, the silicone wetting agent, and the ultraviolet curing agent to the solution containing sodium alginate and copper sulfate in step (4), stir and mix, and obtain an aqueous coating solution for the antistatic layer.

[0058] According to the reaction equation ratio of the reducing agent ascorbic acid and glucose to copper sulfate, it can be seen that the copper sulfate in the solution is excessive. At this time, the reducing agent is fully consumed, and the remaining copper sulfate in the solution can provide sufficient antibacterial copper ions. The remaining components are added to the solution containing sodium alginate and copper sulfate (remaining) to obtain a coating solution.

[0059] Furthermore, the coating liquid of the primer layer comprises, by weight percentage:

[0060]

[0061]

[0062] The resin to be cross-linked includes isocyanate resin, polyester resin and polyacrylic resin, and the mass ratio of isocyanate resin, polyester resin and polyacrylic resin is (1-5): (1-5): (1-10).

[0063] Furthermore, the coating liquid of the primer layer is prepared by the following steps:

[0064] (1) using a tris(hydroxymethyl)aminomethane hydrochloride solution to adjust the pH value to 8-8.5; wherein the concentration of the tris(hydroxymethyl)aminomethane hydrochloride solution is 0.4-0.8% (w / v);

[0065] (2) adding polydopamine to the solution of step (1) and stirring thoroughly;

[0066] (3) adding branched polyethyleneimine to the solution of step (2) and stirring thoroughly;

[0067] (4) Adding the resin to be cross-linked, the silicone wetting agent, and the ultraviolet curing agent to the solution of step (3) to prepare an aqueous coating solution for the primer layer.

[0068] The alkaline medium environment provided by tris(hydroxymethyl)aminomethane hydrochloride) solution is favorable for the Michael addition reaction of polydopamine and branched polyethyleneimine to form a self-assembled coating which is firmly bonded to the surface of the film substrate and provides a cationic polyelectrolyte.

[0069] The UV curing agent is not particularly limited in the present invention, and can be selected by a person skilled in the art according to actual needs. For example, the UV curing agent is selected from at least one of the commercially available Irgacure 184, Irgacure 2959 and Lucirin TPO. In the antistatic coating liquid and / or the primer coating liquid, the amount of the UV curing agent added is preferably 0.2-1wt%. The silicone wetting agent of the present invention can be selected from the commercially available Maitu 408 (polyether-modified heptamethyl trisiloxane silicone), Digo TEGO270 (polyether siloxane copolymer), TEGO280 (polyether siloxane copolymer), BYK-333 (polyether-modified siloxane), etc.

[0070] The present invention has the advantages that:

[0071] (1) While using the antibacterial combination of copper sulfate, nano-cuprous oxide, and nano-copper oxide, the layered self-assembly system constructed by the primer layer and the electrostatic layer can effectively avoid the excessive release of copper ions, improve the sustained release efficiency, and provide excellent and sustained antibacterial performance. In addition, the layered self-assembly system can improve the surface hydrophilicity of the polyester composite film and enhance the antistatic performance of the polyester film.

[0072] (2) Graphene oxide is used to load nano-cuprous oxide and nano-cupric oxide, fully combining the antibacterial advantages of the three and solving the problem of uneven performance caused by the easy agglomeration of nanomaterials.

[0073] (3) In the layered self-assembly system constructed by the primer layer and the electrostatic layer on the surface of the polyester composite film, the similar compatibility of the basic components and the electrostatic force bonding promote a stronger bond between the primer layer and the electrostatic layer, and between the primer layer and the polyester base layer, thereby improving the overall mechanical properties and durability of the composite film. BRIEF DESCRIPTION OF THE DRAWINGS

[0074] By reading the detailed description below with reference to the accompanying drawings, the above and other purposes, features and advantages of the exemplary embodiments of the present disclosure will become readily understood. In the accompanying drawings, several embodiments of the present disclosure are shown in an exemplary and non-limiting manner, and the same or corresponding reference numerals represent the same or corresponding parts, wherein:

[0075] Figure 1 It is a schematic structural diagram of the antistatic and antibacterial biaxially stretched polyester composite film of the present invention.

[0076] Explanation of reference numerals: 1 - antistatic layer; 2 - primer layer; 3 - polyester base layer; 4 - glue layer. DETAILED DESCRIPTION

[0077] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.

[0078] The antistatic and antibacterial biaxially stretched polyester composite film of the present invention comprises the following layers in sequence: an antistatic layer 1, a primer layer 2, a polyester base layer 3 and an optional glue layer 4;

[0079] 1) Antistatic layer 1, thickness 5-20 μm, in parts by weight, comprising:

[0080]

[0081] 2) Primer layer 2, thickness 5-20 μm, in parts by weight, comprising:

[0082]

[0083] 3) Polyester base layer 3, thickness 10-25 μm, preferably PET;

[0084] 4) a glue layer 4 having a thickness of 5-15 μm, comprising a polyurethane resin and an antistatic agent, wherein the antistatic agent comprises an amphoteric antistatic agent, and the content of the antistatic agent accounts for 20-50% of the total mass of the glue layer 4;

[0085] In the antistatic layer 1 and the primer layer 2, the cross-linked resin is prepared by cross-linking and curing -NCO in the isocyanate resin with the polyester resin and the polyacrylic resin, and the mass ratio of the isocyanate resin, the polyester resin and the polyacrylic resin is (1-5): (1-5): (1-10). Preferably, the cross-linked resin of the antistatic layer 1 and the cross-linked resin of the primer layer 2 are prepared by UV cross-linking and co-curing after the composite film is biaxially stretched.

[0086] The polyester resin used in the present invention is obtained by polycondensation of at least one component selected from terephthalic acid, phthalic anhydride and trimellitic anhydride and at least one component selected from ethylene glycol, propylene glycol, glycerol, 1,6-hexanediol and 1,2-butanediol.

[0087] The polyacrylic acid resin used in the present invention is prepared by polymerizing at least one of methyl methacrylate, ethyl methacrylate, n-butyl methacrylate and acrylamide.

[0088] The isocyanate resin used in the present invention is prepared by polymerizing at least one of toluene diisocyanate, diphenylmethane diisocyanate, polymethylene polyphenyl polyisocyanate, hexylene diisocyanate, xylylene diisocyanate and isophorone diisocyanate.

[0089] The surface of the graphene oxide of the present invention is preferably deposited with nano-copper oxide and nano-cuprous oxide, the total mass ratio of the nano-copper oxide and nano-cuprous oxide to the mass ratio of the graphene oxide is 1: (10-20); the particle size of the nano-copper oxide and nano-cuprous oxide is ≤50nm. The nano-copper oxide and nano-cuprous oxide are deposited by the following steps:

[0090] (1) preparing a copper salt solution with a mass percentage concentration of 5-15%, dividing it into two parts, adding graphene oxide to the first copper salt solution, and ultrasonically shaking and stirring at high speed;

[0091] (2) adding polyethylene glycol to the first copper salt solution, stirring and drying at 80-120° C., treating at 500-600° C. for 1-2 h, and grinding to obtain graphene oxide-nano copper oxide powder;

[0092] (3) dispersing the graphene oxide-nano copper oxide powder obtained in step (2) in the second copper salt solution;

[0093] (4) preparing a sodium alginate solution with a mass percentage concentration of 5-15%, adding the copper salt solution of step (3) into the sodium alginate solution, adding a reducing agent and reacting for 20-60 minutes to obtain graphene oxide with nano-copper oxide and nano-cuprous oxide deposited on the surface.

[0094] On the other hand, the present invention also provides a method for preparing an antibacterial and antistatic biaxially stretched polyester film, comprising the following steps:

[0095] S1: Using polyester masterbatch to heat and melt through an extruder, extruding from a T-die to form a film, and cooling and shaping on a chilled roller at 20-25°C to obtain a polyester base layer 3; preferably, a high gloss film-grade PET masterbatch is used, and the surface of the polyester base layer 3 is subjected to corona discharge treatment before coating;

[0096] S2: applying the coating liquid of the primer layer 2 to a surface of the polyester base layer 3, pre-drying, and stretching at 80-90° C. along a first direction, for example, stretching 2-4 times along a machine direction (MD); wherein, by weight percentage, the coating liquid of the primer layer 2 comprises: 10-20% of a resin to be cross-linked, 5-15% of polydopamine, 5-15% of branched polyethyleneimine, 2-5% of an organosilicon wetting agent, 1-10% of tris(hydroxymethyl)aminomethane hydrochloride, 0.2-1% of an ultraviolet curing agent, and 35-76% of deionized water; the pre-drying comprises pre-curing and drying using ultraviolet light, and the degree of curing is controlled at 10-30%;

[0097] The coating liquid of the primer layer 2 is prepared by the following steps:

[0098] (1) Using tris(hydroxymethyl)aminomethane hydrochloride) solution, the pH value was adjusted to 8-8.5;

[0099] (2) adding polydopamine to the solution of step (1) and stirring thoroughly;

[0100] (3) adding branched polyethyleneimine to the solution of step (2) and stirring thoroughly;

[0101] (4) adding the resin to be cross-linked, the silicone wetting agent, and the ultraviolet curing agent to the solution of step (3) to prepare an aqueous coating solution for the primer layer 2;

[0102] S3: applying the coating liquid of the antistatic layer 1 to the outer surface of the primer layer 2, and at the same time applying the glue layer 4 to the surface of the polyester base layer 3 opposite to the primer layer 2, pre-drying, stretching in a second direction perpendicular to the first direction, for example, stretching in the transverse direction (TD) by 3-4 times, and heat-treating and shaping in a tentering machine;

[0103] The coating liquid of the antistatic layer 1 comprises: 10-20% of the resin to be cross-linked, 5-15% of sodium alginate, 5-15% of graphene oxide, 2-10% of copper sulfate, 2-5% of an organosilicon wetting agent, 0.2-1% of an ultraviolet curing agent, and 35-75% of deionized water; the pre-drying can be performed by heating, for example, heating to 110-150°C at a rate of 1-2°C per second; ultraviolet light pre-curing can also be used, and the curing degree is controlled at 10-30%;

[0104] The coating solution of the antistatic layer 1 is prepared by the following steps:

[0105] (1) preparing a copper sulfate solution with a mass percentage concentration of 5-15%, dividing it into two parts, adding graphene oxide to the first copper sulfate solution, and ultrasonically shaking and stirring at high speed;

[0106] (2) adding polyethylene glycol to the first copper salt solution in which graphene oxide is dispersed, stirring and drying at 80-120° C., treating at 500-600° C. for 1-2 h, and grinding to obtain graphene oxide-nano copper oxide powder;

[0107] (3) dispersing the graphene oxide-nano copper oxide powder obtained in step (2) in a second portion of the copper sulfate solution;

[0108] (4) preparing a sodium alginate solution with a mass percentage concentration of 5-15%, adding the copper sulfate solution of step (3) to the sodium alginate solution, adding a reducing agent to react for 20-30 minutes, and obtaining graphene oxide with nano-copper oxide and nano-cuprous oxide deposited on the surface; the reducing agent is ascorbic acid and / or glucose, and the molar ratio of the reducing agent to copper sulfate is 1:(4-8);

[0109] (5) Add the resin to be cross-linked, the silicone wetting agent, and the ultraviolet curing agent to the solution containing sodium alginate and copper sulfate in step (4), stir and mix, and obtain an aqueous coating solution for the antistatic layer 1.

[0110] S4: UV cross-linking and curing to obtain an antistatic and antibacterial biaxially stretched polyester composite film; wherein the UV light source used for UV cross-linking and curing is selected from at least one of a mercury lamp light source, an LED light source, and a xenon lamp light source, and the curing energy is 2000-12000 mJ / cm2 .

[0111] Example 1

[0112] The antistatic and antibacterial biaxially stretched polyester composite film of this embodiment comprises the following layers in sequence: an antistatic layer 1, a primer layer 2, a polyester base layer 3 and a glue layer 4;

[0113] 1) Antistatic layer 1, thickness 10 μm, in parts by weight, comprising:

[0114]

[0115] UV curing agent

[0116] 2) Primer layer 2, thickness 8 μm, comprising, by weight:

[0117]

[0118] In the cross-linked resin of the antistatic layer 1 and the primer layer 2, the mass ratio of isocyanate resin, polyester resin and polyacrylic resin is 4:5:6;

[0119] 3) PET base layer 3, thickness 12 μm;

[0120] 4) Glue layer 4, with a thickness of 5 μm, comprises, by weight, 15 parts of polyurethane resin, 15 parts of amphoteric antistatic agent and 3 parts of organosilicon wetting agent.

[0121] The specific preparation method comprises the following steps:

[0122] S1: Hengyi bright film-grade PET masterbatch is heated and melted by an extruder. When the melt flows through the die lip from the T-die, it is cooled and shaped on a chilled roller under the action of a high-voltage electrostatic adsorption system. The chilled roller temperature is 25°C to obtain a polyester base material, and the polyester base material is subjected to double-sided corona discharge treatment;

[0123] S2: The coating liquid of the primer layer is coated (by rod coating method) on one surface of the polyester base layer, and the primer layer is pre-cured and dried by ultraviolet light. The UV light source is LED light source, and the curing energy is about 5000mJ / cm 2 , the curing amount is controlled at about 20%; the sheet is preheated to 85°C and stretched 3.5 times in the machine direction (MD);

[0124] S3: applying the coating liquid of the antistatic layer to the outer surface of the primer layer, and applying a glue layer to the surface of the polyester base layer opposite to the primer layer; heating to 120°C at 1°C per second, and then heating to 150°C at 2°C per second for preheating and drying, stretching 3.2 times in the transverse direction (TD), and heat treatment and shaping in a tentering machine;

[0125] S4: UV cross-linking and curing to obtain an antistatic and antibacterial biaxially stretched polyester composite film; wherein the UV light source adopts an LED light source, and the curing energy is about 10000mJ / cm 2 .

[0126] Example 2

[0127] The main difference between this embodiment and embodiment 1 is that the material ratios of the antistatic layer 1 and the primer layer 2 are different. Specifically, the following are included:

[0128] 1) Antistatic layer 1, thickness 10 μm, in parts by weight, comprising:

[0129]

[0130] 2) Primer layer 2, thickness 8 μm, comprising, by weight:

[0131]

[0132]

[0133] In the cross-linked resin of the antistatic layer 1 and the primer layer 2, the mass ratio of isocyanate resin, polyester resin and polyacrylic resin is 4:5:6;

[0134] 3) PET base layer 3, thickness 12 μm;

[0135] 4) Glue layer 4, with a thickness of 5 μm, comprises, by weight, 15 parts of polyurethane resin, 15 parts of amphoteric antistatic agent and 3 parts of organosilicon wetting agent.

[0136] Example 3

[0137] The difference between this embodiment and embodiment 2 is that: 1) the graphene oxide in the antistatic layer 1 is loaded with nano copper oxide; 2) the material ratio of the antistatic layer 1 and the primer layer 2 is different. Specifically including:

[0138] The main difference between this embodiment and embodiment 1 is that the material ratios of the antistatic layer 1 and the primer layer 2 are different. Specifically, the following are included:

[0139] 1) Antistatic layer 1, thickness 10 μm, in parts by weight, comprising:

[0140]

[0141] 2) Primer layer 2, thickness 8 μm, comprising, by weight:

[0142]

[0143] In the cross-linked resins of the antistatic layer 1 and the primer layer 2, the mass ratio of isocyanate resin, polyester resin and polyacrylic resin is 2:3:5;

[0144] 3) PET base layer 3, thickness 12 μm;

[0145] 4) Glue layer 4, with a thickness of 5 μm, comprises, by weight, 15 parts of polyurethane resin, 15 parts of amphoteric antistatic agent and 3 parts of organosilicon wetting agent.

[0146] As for the preparation method, the main difference lies in the coating liquid of the antistatic layer, which specifically includes the following steps:

[0147] (1) preparing a copper sulfate solution with a mass percentage concentration of 15%, dividing it into two parts, adding graphene oxide to the first copper sulfate solution, and performing ultrasonic vibration and high-speed stirring;

[0148] (2) adding polyethylene glycol to the first solution in which graphene oxide is dispersed, stirring and filtering at 80° C. to obtain a gel, heating to 120° C. to dry, treating at 550° C. for 1 h, and grinding to obtain graphene oxide-nano copper oxide powder, wherein the mass ratio of nano copper oxide to graphene oxide is about 1:15, and the particle size of nano copper oxide is about 20-50 nm;

[0149] (3) dispersing the graphene oxide-nano copper oxide powder obtained in step (2) in the second portion of the copper sulfate solution, adding sodium alginate, the resin to be cross-linked, a silicone wetting agent, and a UV curing agent, stirring and mixing to obtain an aqueous coating solution for an antistatic layer.

[0150] Example 4

[0151] The difference between this embodiment and embodiment 3 is that the graphene oxide in the antistatic layer 1 is loaded with nano-cuprous oxide. As for the preparation method, the main difference is that the coating liquid of the antistatic layer is different, and specifically includes the following steps:

[0152] (1) preparing a copper sulfate solution with a mass percentage concentration of 15%, adding graphene oxide, and performing ultrasonic vibration and high-speed stirring;

[0153] (2) preparing a sodium alginate solution with a mass percentage concentration of 10%, adding the copper sulfate solution of step (3) to the sodium alginate solution, adding ascorbic acid and reacting for 25 minutes to obtain graphene oxide with nano-cuprous oxide deposited on the surface, and the copper sulfate in the solution is not completely reacted; the mass ratio of nano-cuprous oxide to graphene oxide is about 1:18, and the particle size of nano-cuprous oxide is about 10-30 nm;

[0154] (3) Add the resin to be cross-linked, the silicone wetting agent, and the ultraviolet curing agent to the solution containing sodium alginate and copper sulfate in the step, and stir and mix to obtain an aqueous coating solution for the antistatic layer.

[0155] Example 5

[0156] The difference between this embodiment and embodiments 3 and 4 is that the surface of graphene oxide in the antistatic layer 1 is loaded with nano cuprous oxide and nano cupric oxide. As for the preparation method, the main difference is that the coating liquid of the antistatic layer is different, and specifically includes the following steps:

[0157] (1) preparing a copper sulfate solution with a mass percentage concentration of 15%, dividing it into two parts, adding graphene oxide to the first copper sulfate solution, and performing ultrasonic vibration and high-speed stirring;

[0158] (2) adding polyethylene glycol to the first copper salt solution in which graphene oxide is dispersed, stirring and filtering at 80° C. to obtain a gel, heating to 120° C. to dry, treating at 550° C. for 1 h, and grinding to obtain graphene oxide-nano copper oxide powder;

[0159] (3) dispersing the graphene oxide-nano copper oxide powder obtained in step (2) in a second portion of the copper sulfate solution;

[0160] (4) preparing a sodium alginate solution with a mass percentage concentration of 10%, adding the copper sulfate solution of step (3) to the sodium alginate solution, adding ascorbic acid and reacting for 25 minutes to obtain graphene oxide with nano-copper oxide and nano-cuprous oxide deposited on the surface, and the copper sulfate in the solution is not completely reacted; the total mass ratio of the nano-copper oxide and nano-cuprous oxide to the mass ratio of the graphene oxide is about 1:15, and the particle size of the nanoparticles is about 10-50 nm;

[0161] (5) Add the resin to be cross-linked, the silicone wetting agent, and the ultraviolet curing agent to the solution containing sodium alginate and copper sulfate in step (4), stir and mix, and obtain an aqueous coating solution for the antistatic layer.

[0162] Comparative Example 1

[0163] The main difference between this comparative example and Example 2 is that the antistatic layer does not contain sodium alginate, graphene oxide and copper sulfate.

[0164] Comparative Example 2

[0165] The main difference between this comparative example and comparative example 1 is that: further, the primer layer does not contain polydopamine and branched polyethyleneimine.

[0166] The main material compositions of the samples of Examples 1-5 and Comparative Examples 1-2 can be found in Table 1, and the raw material compositions can be found in Table 2.

[0167] Table 1 Main material composition of samples of Examples 1-5 and Comparative Examples 1-2

[0168]

[0169]

[0170] Table 2 Raw material composition of samples of Examples 1-5 and Comparative Examples 1-2

[0171]

[0172]

[0173] Performance test and method:

[0174] (1) Volume resistivity: Use a resistivity meter to measure the volume resistivity ρ by two-point detection method. v :

[0175]

[0176] In formula (I): Rv is the measured volume resistance, S is the cross-sectional area of ​​the film test, and L is the length of the film sample.

[0177] (2) Water contact angle: The hydrophilicity of the antistatic layer of the polyester composite film was evaluated using the OCA15EC video optical contact angle meter from German dataphysics.

[0178] (3) Antibacterial performance test:

[0179] The antibacterial activity of the film to be tested against Escherichia coli and Staphylococcus aureus was determined by the bacterial counting method. After diluting the bacterial solution (105 CFU) with liquid culture medium (PBS buffer), 0.1g of blank filter paper and 0.1g of the film sample to be tested were added respectively, and the culture was shaken and cultured for 24 hours. The cultured bacterial solution was diluted 100 times with phosphate buffer solution. More than 100 μL of the diluted bacterial solution was evenly coated on the Luria Bertani (LB) agar plate and cultured in a 37°C incubator for 24 hours.

[0180] Reduction of bacteria (%) = (a - b) / a × 100% Formula (II);

[0181] In formula (II), a and b are the colony counts formed on the agar plate after the bacterial solution co-cultured with the blank filter paper and the film sample to be tested is diluted and coated.

[0182] (4) Ethanol resistance:

[0183] The object to be tested was soaked with ethanol, and then a load of 5 kg was placed on the surface of the film. The load was dragged horizontally 10 times, and the resistivity change of the film surface was recorded to evaluate the firmness of the film surface coating.

[0184] □: The change of antistatic performance is less than 10 2 ;

[0185] ○: Change in antistatic properties is greater than 10 2 Less than 10 11 ;

[0186] ▲: The change of antistatic performance is greater than 10 11 .

[0187] (5) Sustained release effect test:

[0188] The antibacterial activity of the film to be tested against Escherichia coli and Staphylococcus aureus was determined by bacterial counting method. The bacterial solution (10 5 CFU), add 0.1g blank filter paper and 0.1g film sample to be tested, shake and culture for 24h. Dilute the cultured bacterial solution 100 times with phosphate buffer solution. Evenly spread 100μL of the diluted bacterial solution on Luria Bertani (LB) agar plate and culture in a 37℃ incubator for 24h. The cultured samples were placed for 0 days, 15 days, 30 days, 45 days, and 60 days, and the antibacterial activity of the film against Escherichia coli and Staphylococcus aureus was determined by bacterial counting method.

[0189] The test results of Examples 1-5 and Comparative Examples 1-2 are shown in Tables 3-4.

[0190] Table 3

[0191]

[0192]

[0193] Table 4

[0194]

[0195] According to the test results, compared with Comparative Example 1, the construction of the hierarchical self-assembly system in Examples 1-5 significantly improved the hydrophilicity of the surface of the multilayer polyester composite film and improved the antistatic performance (the volume resistivity was significantly reduced, showing a value of less than 10 8 The film has a volume resistivity of Ω.cm and good antibacterial properties (the antibacterial rate against Escherichia coli and Staphylococcus aureus is higher than 95%), and excellent long-lasting antibacterial properties (the antibacterial test results for 60 days are all higher than 90%).

[0196] Specifically, in Examples 1-5, Examples 1-2 have a higher content of cross-linked resin in the antistatic layer relative to Examples 3-5, and its hydrophilicity and antibacterial properties are slightly lower. While ensuring the comprehensive properties such as the mechanical properties of the composite film, the content of hydrophilic substances and antibacterial substances in the antistatic layer is increased, which can effectively improve the antistatic and antibacterial properties of the composite film. Secondly, on the basis of using copper sulfate, nano-copper oxide / nano-cuprous oxide is further used, especially the sample of Example 5 in which nano-copper oxide and nano-cuprous oxide are loaded on the surface of graphene oxide, which reflects a more excellent antibacterial persistence, that is, a better sustained release effect. In comparison, because Comparative Examples 1-2 do not contain hydrophilic components and antibacterial components, their comprehensive performance cannot meet the antistatic and antibacterial requirements.

[0197] In general, the composite film of the present invention effectively improves the antistatic performance and also achieves a satisfactory antibacterial effect, and has great market application potential.

[0198] The above introduces the preferred embodiments of the present invention, which is intended to make the spirit of the present invention clearer and easier to understand, but is not intended to limit the present invention. All modifications, substitutions, and improvements made within the spirit and principles of the present invention should be included in the scope of protection outlined by the claims attached to the present invention.

Claims

1. A method for preparing an antistatic and antibacterial biaxially oriented polyester composite film, characterized in that: The polyester composite film comprises the following layers in sequence: an antistatic layer, a primer layer and a polyester base layer; The antistatic layer has a thickness of 5-20 μm and comprises, by weight: The primer layer, with a thickness of 5-20 μm, comprises, by weight: Polyester base layer, thickness 10-25μm; Nano-copper oxide and nano-cuprous oxide are deposited on the surface of the graphene oxide; The cross-linked resin is prepared by cross-linking and curing -NCO in isocyanate resin with polyester resin and polyacrylic resin, and the mass ratio of isocyanate resin, polyester resin and polyacrylic resin is (1-5): (1-5): (1-10); The preparation method of the polyester composite film comprises the following steps: S1: using polyester masterbatch to melt and extrude into film through an extruder, and cooling and shaping on a chilled roller to obtain a polyester base layer; S2: applying the coating liquid of the primer layer to a surface of the polyester base layer, pre-drying, and stretching along a first direction; S3: applying the coating liquid of the antistatic layer to the outer surface of the primer layer, pre-drying, stretching along a second direction perpendicular to the first direction, and heat treating to fix the shape; S4: UV cross-linking and curing to obtain an antistatic and antibacterial biaxially stretched polyester composite film; Wherein, the coating liquid of the antistatic layer is prepared by the following steps: (1) preparing a copper sulfate solution with a mass percentage concentration of 5-15%, dividing it into two parts, adding graphene oxide to the first copper sulfate solution, and ultrasonically shaking and stirring at high speed; (2) adding polyethylene glycol to the first copper salt solution in which graphene oxide is dispersed, stirring and drying at 80-120° C., treating at 500-600° C. for 1-2 h, and grinding to obtain graphene oxide-nano copper oxide powder; (3) dispersing the graphene oxide-nano copper oxide powder obtained in step (2) in a second portion of the copper sulfate solution; (4) preparing a sodium alginate solution with a mass percentage concentration of 5-15%, adding the copper sulfate solution of step (3) to the sodium alginate solution, adding a reducing agent to react for 20-30 minutes, and obtaining graphene oxide with nano-copper oxide and nano-cuprous oxide deposited on the surface; the reducing agent is ascorbic acid, and the molar ratio of the reducing agent to copper sulfate is 1:(4-8); (5) Add the resin to be cross-linked, the silicone wetting agent, and the ultraviolet curing agent to the solution containing sodium alginate and copper sulfate in step (4), stir and mix, and obtain an aqueous coating solution for the antistatic layer.

2. The method for preparing a polyester composite film according to claim 1, wherein: The cross-linked resin of the antistatic layer and the cross-linked resin of the primer layer are prepared by ultraviolet cross-linking and co-curing after the composite film is biaxially stretched.

3. The method for preparing a polyester composite film according to claim 1, characterized in that: The surface of the polyester base layer opposite to the primer layer also includes a glue layer with a thickness of 5-15 μm, which includes polyurethane resin and antistatic agent. The antistatic agent includes an amphoteric antistatic agent, and the content accounts for 20-50% of the total mass of the glue layer.

4. The method for preparing a polyester composite film according to any one of claims 1 to 3, characterized in that: The total mass ratio of the nano-copper oxide and the nano-cuprous oxide to the mass ratio of the graphene oxide is 1:(10-20); the particle size of the nano-copper oxide and the nano-cuprous oxide is ≤50nm.

5. The method for preparing a polyester composite film according to claim 4, characterized in that: By weight percentage, the coating liquid of the antistatic layer comprises: The resin to be cross-linked includes isocyanate resin, polyester resin and polyacrylic resin. The mass ratio of isocyanate resin, polyester resin and polyacrylic resin is (1-5): (1-5): (1-10)。 6. The method for preparing a polyester composite film according to claim 1, characterized in that: By weight percentage, the coating liquid of the primer layer comprises: The resin to be cross-linked includes isocyanate resin, polyester resin and polyacrylic resin. The mass ratio of isocyanate resin, polyester resin and polyacrylic resin is (1-5): (1-5): (1-10)。 7. The method for preparing a polyester composite film according to claim 6, characterized in that: The coating liquid of the primer layer is prepared by the following steps: (1) Using tris(hydroxymethyl)aminomethane hydrochloride) solution, the pH value was adjusted to 8-8.5; (2) adding polydopamine to the solution of step (1) and stirring thoroughly; (3) adding branched polyethyleneimine to the solution of step (2) and stirring thoroughly; (4) Adding the resin to be cross-linked, the silicone wetting agent, and the ultraviolet curing agent to the solution of step (3) to prepare an aqueous coating solution for the primer layer.

Citation Information

Patent Citations

  • Antistatic polyester film

    CN213113177U

  • Preparation method of alginate-graphene-nano cuprous oxide composite antibacterial film

    CN105561403A

  • Layer-by-layer self-assembled slow-release antibacterial polymer separation membrane as well as preparation method and application thereof

    CN114904402A